The computer revolution in Canada : building national technological competence - Vardalas, John N. (History of computing., 2001)
The forces that shaped Canada's digital innovations in the postwar period. After World War II, other major industrialized nations responded to the technological and industrial hegemony of the United States by developing their own design and manufacturing competence in digital electronic technology. In this book John Vardalas describes the quest for such competence in Canada, exploring the significant contributions of the civilian sector but emphasizing the role of the Canadian military in shaping radical technological change. As he shows, Canada's determination to be an active participant in research and development work on advanced weapons systems, and in the testing of those weapons systems, was a cornerstone of Canadian technological development during the years 1945-1980. Vardalas presents case studies of such firms as Ferranti-Canada, Sperry Gyroscope of Canada, and Control Data of Canada. In contrast to the standard nationalist interpretation of Canadian subsidiaries of transnational corporations as passive agents, he shows them to have been remarkably innovative and explains how their aggressive programs to develop all-Canadian digital R & D and manufacturing capacities influenced technological development in the United States and in Great Britain. While underlining the unprecedented role of the military in the creation of peacetime scientific and technical skills, Vardalas also examines the role of government and university research programs, including Canada's first computerized systems for mail sorting and airline reservations. Overall, he presents a nuanced account of how national economic, political, and corporate forces influenced the content, extent, and direction of digital innovation in Canada.